Factors Affecting Entrepreneurial Intention of Students in Agricultural Sector - Sahni, Apoorva; Janjhua, Yasmin; Sharma, Krishan Kumar (International Journal of Economic Plants, 2020)
India being an agrarian country, with tremendous natural resources, agricultural sector of the country is a potential business area to be developed by youth. Agricultural sector can be enhanced more through agripreneurial activities. This study provides an insight into the factors that have an effect on the entrepreneurship intention of agricultural students. It would serve as base for future studies and have implications for educators and policy makers.